Contracts and cooperation: The relative failure of the Irish dairy industry in the late nineteenth century reconsidered - Ingrid Henriksen; Eoin McLaughlin; Paul Sharp (European Historical Economics Society (EHES), 2015)
Why did the establishment of cooperative creameries in late nineteenth century Ireland fail to halt the relative decline of her dairy industry compared to other emerging producers? This paper compares the Irish experience with that of the market leader, Denmark, and shows how each adopted the cooperative organisational form, but highlights that an important difference was institutional: specifically regarding the enforcement of vertically binding contracts, which are considered to be of vital importance for the successful operation of cooperatives. We argue that this failure, combined with a strong proprietary sector which was opposed to cooperation, reinforced the already difficult conditions for dairying in Ireland due to poor social capital.
Keywords: K12; L31; N43; N53; Q13; 330; Contracts; cooperation; dairying; Ireland